KONSEP NAFKAH MENURUT MUHAMMAD SYAHRUR DAN KOMPILASI HUKUM ISLAM - Riyan Erwin Hidayat; Muhammad Nur Fathoni (Institut Agama Islam Negeri Metro, 2022)
Livelihood is meeting the needs of food, shelter, and the wife's treatment, and it is clear that a husband is obliged to provide maintenance to his wife. Based on the law, maintenance is a husband's obligation to his wife that must be met in the form of household needs in accordance with the husband's ability. However, at present, there are various disputes regarding what conditions are included in subsistence, especially in terms of types of subsistence. Therefore, this research is a study that discusses the concept of living according to Muhammad Syahrur and the Compilation of Islamic Law. About how the relevance of his thoughts. To know the relevance of Muhammad Syahrur and the Compilation of Islamic Law regarding maintenance. The type of research used is library research, so the research is not a